2014
DOI: 10.1038/nprot.2014.051
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and quantification of protein synthesis in cultured cells and whole tissues by puromycin-associated nascent chain proteomics (PUNCH-P)

Abstract: Regulation of mRNA translation has a pivotal role in modulating protein levels, and the genome-wide identification of proteins synthesized at a given time is indispensable to our understanding of gene expression. This protocol describes the mass-spectrometric analysis of newly synthesized proteins from cultured cells or whole tissues by using a biotinylated derivative of puromycin, which becomes incorporated into nascent polypeptide chains by ribosome catalysis. In this method, termed puromycin-associated nasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 25 publications
0
69
0
Order By: Relevance
“…Next, we used the nonradioactive SUnSET method to analyze protein synthesis. 20 In this method, low doses of puromycin are incorporated into neosynthesized peptides [20][21][22] and are monitored by flow cytometry to deduce protein translation rates. The puromycin fluorescence was not significantly changed after 24 hours of Sal treatment, confirming similar levels of total protein synthesis (supplemental Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we used the nonradioactive SUnSET method to analyze protein synthesis. 20 In this method, low doses of puromycin are incorporated into neosynthesized peptides [20][21][22] and are monitored by flow cytometry to deduce protein translation rates. The puromycin fluorescence was not significantly changed after 24 hours of Sal treatment, confirming similar levels of total protein synthesis (supplemental Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Emetine was used to arrest elongating ribosomes to prevent ribosomal run-off. It has been shown that emetine does not interfere with the incorporation of puromycin into nascent chains (24). Total cell extracts were clarified by centrifugation at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…The reaction was terminated, and RNCs were disassembled by addition of 1 ml of urea/SDS denaturing buffer (50 mM Tris-HCl, pH 7.5, 8 M urea, 2% SDS, and 200 mM NaCl). Biotin-puromycin-labeled nascent chains were recovered by streptavidin-agarose beads, following the PUNCH approach (24). The recovery efficiency was examined by immunoblotting analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this approach still provides indirect evidence for the presence of a specific sPEP, since the observed interaction of an ORF with ribosomes does not necessarily imply translation of that ORF, but it can also function in regulating the translation of other ORFs. Cutting-edge techniques such as puromycin-associated nascent chain proteomics (PUNCH-P) allowing intact ribosome-nascent polypeptide chains to be analyzed by mass spectrometry (Aviner et al, 2014) could overcome this problem, but are not yet been optimized for plants. The most direct evidence for the presence of peptides in planta can be obtained from mass spectrometry analyses.…”
Section: Peptides Encoded By Sorfs In Primary Transcripts Of Mirnasmentioning
confidence: 99%